MicroRNA in situ hybridization in the human entorhinal and transentorhinal cortex - Nelson, Peter T.; Dimayuga, James; Wilfred, Bernard R. (Frontiers in Human Neuroscience, 2010)
MicroRNAs (miRNAs) play key roles in gene expression regulation in both healthy and disease brains. To better understand those roles, it is necessary to characterize the miRNAs that are expressed in particular cell types under a range of conditions. In situ hybridization (ISH) can demonstrate cell- and lamina-specific patterns of miRNA expression that would be lost in tissue level expression profiling. In the present study, ISH was performed with special focus on the human entorhinal cortex (EC) and transentorhinal cortex (TEC). The TEC is the area of the cerebral cortex that first develops neurofibrillary tangles in Alzheimer’s disease (AD). However, the reason for TEC’s special vulnerability to AD-type pathology is unknown. MiRNA ISH was performed on three human brains with well-characterized clinical and pathological parameters. Locked nucleic acid ISH probes were used referent to miR-107, miR-124, miR-125b, and miR-320. In order to correlate the ISH data with AD pathology, the ISH staining was compared with near-adjacent slides processed using Thioflavine stains. Not all neurons or cortical lamina stain with equal intensity for individual miRNAs. As with other areas of brain, the TEC and EC have characteristic miRNA expression patterns. MiRNA ISH is among the first methods to show special staining characteristics of cells and laminae of the human TEC.